Characterization and inventory of PBDD/F emissions from deca-BDE, polyethylene (PE) and metal blends during the pyrolysis process. (April 2017) - Mei, Jun; Wang, Xiuji; Xiao, Xiao; Cai, Ying; Tang, Yuhui; Chen, Pei
Highlights: Characterization of PBDD/Fs formed from pyrolysis of PE, metal and deca-BDE blends was studied. The study can add a new dimension to PBDD/Fs formed during thermal treatment of WEEE. Abstract: The thermal treatment of waste electrical and electronic equipment (WEEE) is regarded as the largest potential contributor to the environmental release of polybrominated dibenzo-p-dioxins/dibenzofurans (PBDD/Fs). Herein, the pyrolysis of decabromodiphenyl ether (deca-BDE), polyethylene (PE) and metal blends was conducted to investigate the emission characteristics of PBDD/Fs at different thermal treatment conditions. The total yield of polybrominated dibenzo-p-dioxins (PBDDs) was less than that of polybrominated dibenzofurans (PBDFs) during the pyrolysis of the PE matrix and metal blends. 2, 3, 7, 8-TBDF and 1, 2, 3, 7, 8-PBDF were the dominant congeners emitted from the pyrolysis. Temperature, presence of oxygen and type of added metal were the critical influencing factors for the PBDD/F formation rates and speciation in the pyrolysis process.